2016
DOI: 10.1080/03235408.2016.1157378
|View full text |Cite
|
Sign up to set email alerts
|

Detection of virulence and pathogenicity genes in selected phytopathovars

Abstract: Plant pathogenic organisms are known to infect host cell using various range of secretory proteins. Amongst all other secretion systems, type III secretion system (T3SS) is a key mechanism for bacterial pathogenesis for establishing and maintaining infection into the host. Expression levels of seven genes viz. avrXacE1, avrXacE2, hpaA and hrpG along with bacterial endogenous control lrp (leucineresponsive protein) were studied. The pathogenic organisms selected for the present study includes Enterobacter cloac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
1
0
4
Order By: Relevance
“…Bakteri menimbulkan penyakit salah satunya karena mempunyai faktor patogenesitas dan tingkat patogenesitas dipengaruhi oleh faktor virulensi (Joko et al, 2014). Beberapa faktor penentu patogenesitas bakteri patogen tanaman antara lain sistem sekresi tipe I-VI (Rakhashiya et al, 2016), eksopolisakarida (EPS) dan lipopolisakarida (LPS) (Arwiyanto, 2015). T3SS merupakan mekanisme penting dalam patogenesitas bakteri Gram negatif patogen tanaman (Rakhashiya et al, 2016).…”
Section: Patogenisitas Bakteri Xanthomonas Oryzae Pv Oryzaeunclassified
See 1 more Smart Citation
“…Bakteri menimbulkan penyakit salah satunya karena mempunyai faktor patogenesitas dan tingkat patogenesitas dipengaruhi oleh faktor virulensi (Joko et al, 2014). Beberapa faktor penentu patogenesitas bakteri patogen tanaman antara lain sistem sekresi tipe I-VI (Rakhashiya et al, 2016), eksopolisakarida (EPS) dan lipopolisakarida (LPS) (Arwiyanto, 2015). T3SS merupakan mekanisme penting dalam patogenesitas bakteri Gram negatif patogen tanaman (Rakhashiya et al, 2016).…”
Section: Patogenisitas Bakteri Xanthomonas Oryzae Pv Oryzaeunclassified
“…Beberapa faktor penentu patogenesitas bakteri patogen tanaman antara lain sistem sekresi tipe I-VI (Rakhashiya et al, 2016), eksopolisakarida (EPS) dan lipopolisakarida (LPS) (Arwiyanto, 2015). T3SS merupakan mekanisme penting dalam patogenesitas bakteri Gram negatif patogen tanaman (Rakhashiya et al, 2016). Keberadaan salah satu atau beberapa faktor penentu patogenesitas dapat menyebabkan bakteri bersifat patogen atau deleterious terhadap inang.…”
Section: Patogenisitas Bakteri Xanthomonas Oryzae Pv Oryzaeunclassified
“…merupakan bakteri endofit pada kilemo (Litsea cubeba) (Ling et al, 2012). Bakteri dari famili yang sama (Brucellaceae) yaitu Ochrobactrum antropi merupakan patogen pada benih Prunus dulcis (Rakhashiya et al, 2016).…”
Section: Alcaligenes Faecalis L48unclassified
“…Beberapa faktor penentu patogenesitas bakteri patogen tanaman antara lain sistem sekresi tipe I-VI (Rakhashiya et al, 2016), eksopolisakarisa (EPS) dan lipopolisakarida (LPS) (Arwiyanto, 2014). T3SS merupakan mekanisme penting dalam patogenesitas bakteri Gram negatif patogen tanaman (Rakhashiya et al, 2016). Keberadaan salah satu atau beberapa faktor penentu patogenesitas dapat menyebabkan bakteri bersifat patogen atau deleterious terhadap inang.…”
Section: Salmonella Bongori Sl9unclassified
“…Mechanisms of pathogenicity of phytopathogens are being extensively studied in Gram-negative and some Gram-positive bacteria (Baker et al , 2010; Venturi and Fuqua, 2013). These studies revealed that pathogens contain suits of genes including various transporter systems (Chen et al , 2010; Rakhashiya et al , 2016; Wilkens, 2015), secretion systems (TSS), virulence and associated metabolism (Abby et al , 2016; Chang et al , 2014; Green and Mecsas, 2016). In pathogens, from the cytoplasm through the inner membrane or the outer membrane to the extracellular space, the secretion of proteins requires dedicated types of machinery, i.e.…”
Section: Introductionmentioning
confidence: 99%